The human histaminergic system in neuropsychiatric disorders. Issue 3 (March 2015) - Shan, Ling; Bao, Ai-Min; Swaab, Dick F.
Highlights: Neuronal histamine production shows a diurnal rhythm, but not in neurodegeneration. The histaminergic system shows alterations in various neuropsychiatric disorders. Animal models for these disorders only partly mimic these histaminergic alterations. Thus, postmortem human brain material is crucial to study these disorders. Abstract : Histaminergic neurons are exclusively located in the hypothalamic tuberomamillary nucleus, from where they project to many brain areas. The histaminergic system is involved in basic physiological functions, such as the sleep–wake cycle, energy and endocrine homeostasis, sensory and motor functions, cognition, and attention, which are all severely affected in neuropsychiatric disorders. Here, we present recent postmortem findings on the alterations in this system in neuropsychiatric disorders, including Parkinson's disease (PD), Alzheimer's disease (AD), Huntington's disease (HD), depression, and narcolepsy. In addition, we highlight the need to validate animal models for these diseases and also for Tourette's syndrome (TS) in relation to alterations in the histaminergic system. Moreover, we discuss the potential for, and concerns over, the use of novel histamine 3 receptor (H3 R) antagonists/inverse agonists as treatment for such disorders.